A 0.5-V 1-μW successive approximation ADC. - Sauerbrey, J. (IEEE Journal of solid state circuits)
A successive approximation analog-to-digital converter (ADC) is presented operating at ultralow supply voltages. The circuit is realized in a 0.18-μm standard CMOS technology. Neither low-VT devices nor voltage boosting techniques are used. All voltage levels are between supply voltage VDD and ground VSS. A passive sample-and-hold stage and a capacitor-based digital-to-analog converter are used to avoid application of operational amplifiers, since opamp operation requires higher values for the lowest possible supply voltage. The ADC has signal-to-noise-and-distortion ratios of 51.2 and 43.3 dB for supply voltages of 1 and 0.5 V, at sampling rates of 150 and 4.1 kS/s and power consumptions of 30 and 0.85 μW, respectively. Proper operation is achieved down to a supply voltage of 0.4 V.